Experimental Study of DQPSK Modulation on SDR Platform - Eko Marpanaji; Bamba Riyanto Trilaksono; Armein Z. R. Langi; Adit Kurniawan; Andri Mahendra; Thay Liung (Journal of ICT Research and Applications, 2007)
This Paper addresses Differential Quadriphase Shift Keying (DQPSK) modulation implemented on SDR platform for the development of digital data  communications based on Software-Defined Radio (SDR). DQPSK modulation performance perceived at Packet Error Rate (PER) is evaluated in terms of Eb/No or S/N ratio, carrier frequency, bit rate, gain, roll-off factor of root Nyquist filter or root raised cosine filter, and payload size from delivered data. Based on these results, the smallest PER could be obtained by setting Eb/No value greater than 20 dB, carrier frequency of at least 0,3 MHz, optimum bit rate of 200 kbps, optimum range payload size of 2000 up to 4000 bytes, and roll-off factor of Nyquist or root-raised cosine filter of 0.4.